A primer on familial cancer genetics - Tischkowitz, Marc (Henry Stewart Talks, 2020)
Principles of cancer genetics, Family history assessing including pedigrees, Testing for cancer predisposition, Evaluating risk in cancer genetics, Common inherited cancers including breast, ovarian, and colorectal, Implication of BRCA1/2 in ovary and breast cancers, Colon cancer and Lynch syndrome